Product Quality The Foundation of Brand Image and Repurchase Intention among Ghyoshop Customers in Morowali Regency - Nurnadila, Nurnadila; Auriza, Moh. Zeylo; Zahara, Zakiyah; Wanti, Sri (JURNAL MANAJEMEN MOTIVASI, 2025)
This study analyzes the effect of Product Quality on Brand Image and Repurchase Intention among Ghyoshop customers in Morowali Regency. The research applies a quantitative method with purposive sampling involving 150 respondents. Data collection used a structured questionnaire, and analysis was conducted through Structural Equation Modeling (SEM) using SmartPLS 4. Findings show that Product Quality positively and significantly affects both Brand Image and Repurchase Intention. Additionally, Brand Image significantly influences Repurchase Intention and mediates the relationship between Product Quality and Repurchase Intention. These results emphasize the strategic importance of maintaining product quality and enhancing brand image to foster customer loyalty and retention.